Math (Calculus)

posted by .

Can somebody solve this logarithm problem step by step for me please:

2(lnx)² + lnx-1 = 0


First let y = ln x be a new variable, , and solve the polynomial
2 y^2 + y - 1 = 0
2(y +1)(y - 1/2) = 0
Solutions are
y = -1 or +1/2
Thus x = e^y
and x= 1/e = 0.3679.. OR
e^0.5 = 1.6487..

  • Math (Calculus) -

    tg(x)sec^6(x)dx

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    how would you solve for y in this problem: ln(y-1)-ln2 = x +lnx ln(y-1)-ln2 = x +lnx Solve for y... ln[(y-1)/2]]=x + lnx take the antilog of each side (y-1)/2= e^(x+lnx) solve for y.
  2. math

    I am suppose to simplify the following problems: sqrt(x)/x (isn't that already simplified?
  3. calculus

    (a) find the intervals on which f is incrs or decrs. (b) find the local min/max values of f. (c) find the intervals of concavity and the inflection points. f(x)=(lnx)/sqrtx I took the derivative and got 2-lnx/2x^3/2 take the values …
  4. Math logs

    Solve the system of equations: y= (lnx)^2 + 2 (lnx^2) y = 3ln(1/x^2)+24 Im not sure what to do..
  5. L'Hopital's rule

    Find lim x->1+ of [(1/(x-1))-(1/lnx)]. Here is my work... =(lnx-(x-1)) / ((x-1)(lnx)) =(lnx-1) / (lnx+ (x+1)/x) This becomes(1/x) / ((1/x)+(1/x^2)) which becomes 1/ (1/x^2) This equals 1/2. I understand the answer has to be -1/2, …
  6. Calculus 1

    Find the derivative of y with respect to x. y=(x^6/6)(lnx)-(x^6/36) So far this is what I've gotten: y=(x^6/6)(lnx)-(x^6/36) y=(1/6)x^6(lnx)-(1/36)x^6 y'=(1/6)x^5(1/x)+lnx(x^5)-(1/6)x^5 What do I do now?
  7. calculus

    sorry to ask a second question so soon, but i'm just not getting this one. if f(x)= 3x lnx, then f'(x)=?
  8. Calculus

    Find the derivatives, dy/dx for the following functions. a. x^2y^4 = lnx + 3y b. y = ln(2x^2 + 1) c. y = ln(ãx) d. y = lnx/x e. y = x^2 lnx f. y ß log_2⁡(3x)
  9. Algebra 1--Step-by-Step

    Can someone show me how to solve these step-by-step?
  10. Calculus

    what is the limit as h approaches 0 of ((x+h)^pi-x^pi)/h?

More Similar Questions